Speech Act Analysis of Teacher Talk in Indonesian EFL Classroom: A Case Study at Secondary School - Ghozali, Arinaa Sabilah; Marshalina, Afifah; Hanafi, Muhammad (Jurnal Pendidikan Humaniora, 2024)
This study analyzed teacher talk in Indonesian EFL classroom. The research aimed to investigate the predominant speech act classification employed by the teacher, the factors influencing an EFL teacher using the predominant speech acts, as well as its impact on instructional activities. It applied a qualitative case study involving one English teacher as the participant. The study used Searle’s taxonomy of speech act classification as the instrument. Data were collected from the recording of classroom observation and interview. The finding of this study revealed the frequency of each classification found as the following: 69,4% for directives, 19,4% for representatives, 8,3% for expressives, and 2,8% for commissives. Directive speech acts were the most frequent used by the teacher in the classroom. The study further suggested that creating better classroom management and guiding the students became teacher’s reasons using directive speech act which potentially impacted instructional activities by influencing students’ behavior to be more attentive and engaged, making class operation smoothly, and creating productive and meaningful learning experiences. The results contribute greater insights to the dynamics of teacher-student interactions and may direct the development of effective pedagogical strategies to be used in EFL classrooms.